تتبع انتشار تغييرات التصميم ضمن بيئة نمذجة معلومات البناء - جمال عمران; بسام حسن; لما سعود (Tishreen University, 2018)
يتناول هذا البحث موضوع إدارة تغييرات التصميم ضمن بيئة نمذجة معلومات البناء (BIM) التعاونية المتعددة الاختصاصات. إن دور الBIM المتطور في تصميم الأبنية وازدياد تعقيد عملية التصميم ولد حاجة لتطوير إدارة التغيير بالاعتماد على الBIM. وعلى الرغم من ميزات الBIM الكبيرة في كشف التعارض والتنبيهات ونشر التغييرات في النموذج، إلا أن أدوات الBIM الحالية توفر دعم محدود في إدارة التغييرات ضمن النماذج المتعددة الاختصاصات. تصف هذه الورقة طريقة مطورة لتنسيق ولتتبع انتشار التغيير ضمن بيئة ال BIM المتعددة الاختصاصات. تعتمد الطريقة المطورة على نمذجة التغيير بالاعتماد على الـBIM وعلى استخدام مصفوفة هيكلية التصميم (DSM) المؤسسة على البارامتر لتمثيل مختلف التبعيات بين بارامترات المنشأ وتوظيفها كأداة لتتبع سلسلة من التغييرات المتعاقبة ضمن بيئة الـBIM، وعلى اقتراح آلية لتكامل الBIM مع الDSM برمجيا لدعم عملية تمثيل مرئي لمسارات التغيير ضمن الBIM. شرحت دراسة حالة حقيقية إمكانية تطبيق الطريقة في بيئة الBIM. This paper addresses the subject of design changes management in the context of a multidisciplinary collaborative Building Information Models (BIM) environment. Because of the evolving role of BIM in designing building projects and the increasing complexity of the design process aroused a need to develop change management based on BIM. Despite the great advantages of BIM in the detection of conflict, alerts and propagating changes in the model, but current BIM tools provide limited support in managing changes across multidisciplinary models. This paper describes developed method to coordinate and track changes within a multidisciplinary BIM environment. The developed method depends on modeling the change based on BIM, on using parameter-based design structure matrix to represent the various dependencies between the parameters of building and as tool for tracking a series of successive changes within the BIM environment, and on suggestion of a mechanism for the integration of BIM with the DSM programmatically to support the visual representation of the tracks of change within BIM. Real case study demonstrates the possibilities of method application in BIM environment.